The effect of musical mood induction on pain perception in adult oncology patients - Mosko, Beth, author; LaGasse, Ashley Blythe, advisor; Davis, William B. (William Barron), advisor; Kees, Nathalie L., committee member (Colorado State University. Libraries, 2011)
The purpose of this pilot study was to examine the effect of musically induced mood on the pain perception of cancer patients. Enrolled participants (N=2) were both patients receiving radiation, chemotherapy, or follow up treatment at a local hospital where recruitment took place. During the experiment participants listened to a 20 minute recording of increasingly elative music, and completed questionnaires before and after that measured mood and pain perception. Measurement tools included the SF-McGill Pain Questionnaire, and the Positive and Negative Affect Schedule (PANAS). Due to low sample size, there were no statistically significant results. However, pain decreased in all tests scores for both participants, and negative affect measures also decreased. Suggestions for future research are discussed.
Keywords: music therapy; pain; oncology